Rekonstruksi Kristologi Logos Menjawab Tantangan Dekonstruksi Terma Logosentrisme dalam Tinjauan Biblika - Yosep Belay (Sekolah Tinggi Teologi Anugrah Indonesia, 2022)
The concept of logos in the Christian faith does not only refer to theological ideas but also touches on the issue of the Christian worldview which as a whole refers to Christ as its centrality. The concept is suspected of being a form of logocentrism (grand narrative) that forms polarization and negation of the external world. Through deconstruction readings, contemporary cultural critics criticize Christian logocentrism. The purpose of reading deconstruction is to change the general understanding, both in philosophy, science, and Christian theology strategies regarding logos with two critical approaches. First, criticizing semantics in terms of logos and second, criticizing the politics of the text through which ideology is constructed and has implications for socio-cultural subordination. This article analyzes and reconstructs logos theology and christology in an attempt to address the challenges of deconstruction. The method used by the writer is descriptive analysis and literature review. The results showed that the concept of Christian logos theology was different from Greek philosophy. In relation to the theory of deconstruction, the bivalence system which is the pattern of the semantic system of logos theology provides strict limits on the meaning system so that the assumptions of deconstruction criticism are irrelevant. Meanwhile, the logos christology approach in biblical studies provides answers to the issue of logocentrism in both theological, literary and Christian epistemological contexts. Abstrak Konsep logos dalam iman Kristen tidak hanya mengacu pada gagasan teologis namun juga menyinggung persoalan wawasan dunia Kristen yang secara keseluruan merujuk pada Kristus sebagai sentralitasnya. Konsep tersebut dicurigai sebagai bentuk logosentrisme (narasi besar) yang membentuk polarisasi dan negasi terhadap dunia eksternal. Melalui pembacaan dekonstruksi, kritikus budaya kontemporer mengkritisi logosentrisme Kristen. Tujuan pembacaan dekonstruksi untuk merombak pemahaman umum, baik dalam strategi filsafat, sains, maupun teologi Kristen mengenai logos dengan dua pendekatan kritis. Pertama, mengkritisi semantik pada terma logos dan kedua, mengkritisi politik teks yang melaluinya ideologi dikonstruksikan dan berimplikasi terhadap subordinasi sosial budaya. Artikel ini menganalisis dan merekonstruksi ulang teologi dan kristologi logos dalam usaha untuk menjawab tantangan dekonstruksi. Metode yang dugunakan penulis deskriptif analisis dan kajian literatur. Hasil penelitian menunjukkan konsep teologi logos Kristen berbeda dengan filsafat Yunani. Dalam kaitannya dengan teori dekonstruksi, sistem bivalensi yang menjadi pola sistem semantik teologi logos memberikan batasan tegas pada sistem makna sehingga asumsi kritik dekonstruksi tidak relevan. Sementara pendekatan kristologi logos dalam kajian biblika memberikan jawaban terhadap isu logosentrisme baik dalam konteks teologis, sastra maupun epistemologi Kristen. Kata Kunci: Kristologi. Logos, Logosentrisme, Dekonstruksi.